Coronary Drug Eluting stent: 7 Years’ Experience of Norvic Hospital - Rawat, Bharat; Bhatta, Yadav; Jaiswal, JP; Rajbhandari, Shekhar; Dhakal, Saroj; Bhusal, Laxman; Gurung, Parbati; Acharya, Nandita G (Nepalese Heart Journal, 2008)
Studies have shown marked beneficial effects of coronary drug eluting stents in the prevention of re-stenosis. The present study demonstrates the experience of coronary drug eluting stents in the Norvic-International Hospital since the commencement of the PCI (Pecutaneaus Coronary Intervention) service in 2001.